PENINGKATAN EFISIENSI PENGGUNAAN LAHAN KELOMPOK TANI SUNGKAI PERMAI MELALUI TUMPANG SARI JAGUNG DAN KACANG TANAH DAN PENGENALAN CENDAWAN MIKORIZA ARBUSKULA (CMA) - Yusniwati Yusniwati; Nilla Kristina (Buletin Ilmiah Nagari Membangun)
The Sungkai Permai Lambung Bukik Farmer Group, Padang City, generally cultivates in monoculture, with limited productive land. The land is planted with rice, secondary crops such as corn, and some peanuts. In the past two years, corn farmers often experience crop failures, especially during the rainy season, where the sun shines less due to global climate change. Therefore, diversifying commodities on limited land so that land efficiency increases are significant to prepare the next source of seeds. To support increased land use efficiency, optimal soil conditions are needed. Utilization of Arbuscular Mycorrhizal fungi can improve soil fertility and is expected to become an alternative technology in plant cultivation. Science and technology activities based on the Study Program and the Assisted Nagari (IbPSNB) were carried out in groups of Permai Sungkai Farmers in the form of 1) Counseling on the pattern of corn-peanut intercropping cultivation, and how to make CMA spore cultures, 2). The demonstration plot for corn-peanut intercropping cultivation. Through this activity, farmers finally understood the benefits and patterns of corn-peanut intercropping. Farmers understand the role and method of making CMA spore cultures. Several farmers cultivated corn-peanut intercropping. Two farmers at the demonstration plot managed to harvest corn and peanuts at the same time. Other farmers have failed to harvest corn due to pest attacks but have succeeded in harvesting peanuts so that the losses experienced by farmers are reduced, and they still have stock of seeds for the next planting season.